Scoop and treat: from an historical controversy to the emergency future - Lansiaux, Edouard; Cozzi, Nicholas; Wacht, Oren; Travers, Stéphane; Drouin, Emmanuel; Wiel, Eric (Frontiers in Disaster and Emergency Medicine, 2024)
Within the intricate narrative of emergency medical services (EMS), there lies a rich and evolving history of innovation and strategy, a saga that weaves through the fabric of prehospital emergency care. At the heart of this narrative is a compelling dichotomy, often whimsically encapsulated as the “stay and play” vs. “scoop and run” philosophies. These seemingly polar approaches to emergency care represent a tapestry of diverse opinions and practices, each tailored to its unique environmental context, clinical demands, and the relative availability of prehospital and hospital resources. Our comprehensive review delves into the historical evolution of these notions, tracing their roots from the ancient world to the present day. We cast a particular focus on the French model of “prehospital medicalization” and the Anglophone “Scoop and Run” approach, exploring their distinct trajectories and influences. Additionally, we turn our gaze to the Israeli system, a unique hybrid shaped by the American prehospital framework yet distinctively molded by the region's enduring conflict. By drawing on an array of interviews, historical records, and scholarly discourse, this document presents an in-depth exploration of the development of prehospital emergency medicine and its pivotal role in contemporary healthcare. Through this investigation, we aim to elucidate the historical tensions surrounding these concepts, shedding light on their implications for the landscape of modern emergency medical services and the intricate web of factors that shape their organization.